2016
DOI: 10.1115/1.4032352
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Different Liquid Based Spectrum Beam Splitters for Combined Solar Photovoltaic Thermal Systems

Abstract: In the spectrum beam split approach of combined solar photovoltaic thermal system (PVT), the complete solar spectrum is splitted. The unwanted part of the solar spectrum for photovoltaic (PV) applications is filtered out and is used separately as heat. In this work, some inexpensive, clear, and easily available selective fluids are identified which can be used as both volumetric heat absorbers and selective spectrum filters for C-Si-based PVT. The electrical performance of a C-Si solar PV cell using these flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In this article, the spectral beam splitting mechanism will be achieved by the volumetric absorption combined spectral beam splitter which consists of the infrared light absorber‐fluid based filter and the visible light absorber‐solid based filter. Compared with cooling liquids used in traditional CPV/T systems, the property requirement of the fluid based filter utilized in spectral splitting CPV/T systems is much stricter . Firstly, the fluid based filter should have high transmittance in the silicon‐particular spectral response range, and effectively absorb other wavelengths.…”
Section: Evaluation Of Volumetric Absorption Combined Spectral Beam Smentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, the spectral beam splitting mechanism will be achieved by the volumetric absorption combined spectral beam splitter which consists of the infrared light absorber‐fluid based filter and the visible light absorber‐solid based filter. Compared with cooling liquids used in traditional CPV/T systems, the property requirement of the fluid based filter utilized in spectral splitting CPV/T systems is much stricter . Firstly, the fluid based filter should have high transmittance in the silicon‐particular spectral response range, and effectively absorb other wavelengths.…”
Section: Evaluation Of Volumetric Absorption Combined Spectral Beam Smentioning
confidence: 99%
“…Compared with cooling liquids used in traditional CPV/T systems, the property requirement of the fluid based filter utilized in spectral splitting CPV/T systems is much stricter. 23 Firstly, the fluid based filter should have high transmittance in the silicon-particular spectral response range, and effectively absorb other wavelengths. Moreover, high thermal conductivity and high specific heat capacity as well as low viscosity are required as the fluids will also act as heat transfer fluids for CPV cells.…”
Section: Fluid Based Filtermentioning
confidence: 99%
“…Multifunctional glass structures are developed and experimentally tested for thermal regulations and to reach high PV efficiencies (Cuce et al, 2015a;2014). Chen and Yin (2016) (Joshi et al, 2016). Heat pipes are extensively used for HPV/T cooling applications (Chen et al, 2017).…”
Section: Performance Enhancement Techniques For Hpv/t Collectorsmentioning
confidence: 99%
“…In the literature, many hybrid solar PV/T systems had been designed with optical filters. Some studies had shown that clean fluids like water and organic liquids could be used with the solar PV systems as optical filters [15][16][17]. A. Qahtan et al [18] had examined the possibility of using the Sustainable Glazed Water Film SGWF as spectrum filter for buildings in the Torrid Zone.…”
Section: Optical Filtersmentioning
confidence: 99%
“…Initially, type of the employed PV cells affects the PV module electrical performance. Depending upon the kind of these cells and climatic circumstances, a standard PV module transforms (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) % of the falling solar radiation into electricity. The residue of solar radiation is transferred into heat, which elevates the module temperature and reduces its efficiency [1].…”
Section: Introductionmentioning
confidence: 99%